Preservation of phenolic compounds on dried leaf infusion of Bauhinia forficata Link - Débora Vasconcelos Bastos Marques; Ana Carolina Duó-Bartolomeu; Marília Elias Gallon; Leonardo Gobbo-Neto; Denise Brentan Silva; Bianca Waléria Bertoni; Suzelei de Castro França; Ana Maria Soares Pereira; Silvia Helena Taleb-Contini (Universidade de São Paulo, 2023)
Abstract Bauhinia forficata Link aqueous extract is usually recommended as a phytomedicine to reduce blood glucose levels and its biological activity has been linked to the presence of phenolic compounds from B. forficata preparations. Several drying processes are used in the production of dry herbal extracts, which may influence the chemical composition and efficacy of final herbal medicines. Due to significant chemical changes, defining appropriate drying processes is essential for phytopharmaceutical drug development. In view of this, we analyzed dried B. forficata leaf infusion (BFLI) extracts by HPLC-UV-MSn, followed by molecular networking analysis to evaluate the chemical profiles from dried extracts yielded by freeze-and spray-drying processes. The main metabolites detected included 11 ferulic/isoferulic acid derivatives and 13 glycosylated flavonoids. The qualitative chemical profiles were alike for both drying processes, whereas the relative abundance of some flavonoids was higher using spray-drying. Taken together, our results showed that freeze-and spray-drying preserved the phenolic profile of BFLI and suggested that spray-drying may be the most suitable to obtain its dried products. Along with studying the chemical profiles of dried herbal extracts, evaluating the influence of drying processes on the quality and chemical profiles of final products is pivotal and may benefit future research.